Capital asset pricing model test on the Johannesburg stock exchange - Mokgele, Kabelo Keosi (My University, 2018)
The Capital Asset Pricing Model (CAPM), jointly accredited to Markowitz (1952), Treynor (1961), Sharpe (1964), Lintner (1965) and Mossin (1966), provides that, at equilibrium, the return on all risky assets is attributable to their covariance with the market portfolio. This paper studies whether the CAPM holds for the South African market (represented by the Johannesburg Stock Exchange), by using the methodology developed by Fama and Macbeth (1973). Furthermore, the paper expands on other factors that influence asset returns and interrogates alternative asset pricing models. The findings of the study on individual assets rejects CAPM in the context of South Africa. This is consistent with other empirical studies. CAPM is also rejected for the Industrial Index as well as the Top 40 index. What is interesting to note however, is that for the Resources index, CAPM is validated.
Thesis submitted in fulfillment of the requirements for the degree of Masters of Management in Finance and Investment, Faculty of Commerce, Law and Management Wits Business School, University of the Witwatersrand, February 2018
Keywords: Johannesburg Stock Exchange; Capital assets pricing model